2023
DOI: 10.3390/su15054556
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Asphalt Self-Healing with Colorless Binder and Pigmented Rejuvenator

Abstract: Despite asphalt self-healing with encapsulated rejuvenators having been intensively researched over the last decade, there is still uncertainty about the performance advantages granted by this technology. As a way of adding to the existing set of research methodologies, this study aimed to test the feasibility of a visual method to investigate the working mechanism of encapsulated rejuvenators in the bituminous mixture. For this purpose, clear bituminous mixtures were produced using a colorless synthetic binde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Previous studies found a strong correlation between the performance of the bitumen in the MSCR test and the accumulated deformation of bituminous mixtures [75], which is one of the most important types of distress in asphalt pavements. Thus, often, bio-oils have a lower viscosity than bituminous binders, which can lead to poor rutting resistance [8,76]. Table 5 summarises the results of the MSCR test at 60 °C for the studied binders.…”
Section: Resistance To Permanent Deformation Accumulationmentioning
confidence: 99%
“…Previous studies found a strong correlation between the performance of the bitumen in the MSCR test and the accumulated deformation of bituminous mixtures [75], which is one of the most important types of distress in asphalt pavements. Thus, often, bio-oils have a lower viscosity than bituminous binders, which can lead to poor rutting resistance [8,76]. Table 5 summarises the results of the MSCR test at 60 °C for the studied binders.…”
Section: Resistance To Permanent Deformation Accumulationmentioning
confidence: 99%